Struktur Bahasa pada Toponimi Jalan di Provinsi Bali dan Proyeksi Kulturalnya di Masa Depan - Sholihatin, Endang; Sa’diyah, Ilmatus; Savitri, Adelia; Putri, Adinda Rusdianti Maulani; Octaviani, Marshanda Amelya (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Street toponymy is a linguistic representation that reflects the social and cultural identity of a region. This study aims to examine the language structure used in street naming in Bali Province and project its role and transformation in future cultural contexts. The study was conducted through a linguistic analysis of street names spread across various regions of Bali, focusing on the morphological, syntactic, and semantic elements contained therein. The results of the analysis indicate that street naming in Bali is dominated by elements of regional languages, local figures, religious terms, and strong geographical elements. This structure demonstrates the close link between language and local values ​​of the Balinese people. However, in the face of globalization, tourism, and the digitalization of geographic information systems, the existence and form of these toponyms have the potential to shift. Cultural projections indicate that preserving the linguistic structure in street naming is crucial to maintaining the continuity of Balinese cultural identity amidst changing times. This study emphasizes the importance of integrating culturally aware and forward-looking street naming policies.